(untitled) (Revista Direito em Debate, 2021)
Abstract: The purpose of this paper is to analyze the institute of plea bargain. This is a qualitative work operationalized by bibliographic and documentary research, with an immersion in comparative analysis. Plea bargain was present at various times in history and it is an institute that carries inaccuracies in both conceptual and classificatory aspects, besides the problem of normative dispersion. In comparative law, Italy is a pioneer in the use of the institute. In Brazil, plea bargain receives treatment from a constitutional, utilitarian and probative perspective. It is, therefore, concluded that Plea Bargain is an evolving instrument, particularly based to its conceptual systematization and normative unification.